“Directive Approach” for Chinese Clients Receiving Psychotherapy: Is That Really a Priority? - Ng, Chi Ting Connie; James, Susan (Frontiers in Psychology, 2013)
The academic literature often suggests that Chinese people prefer directive approaches in therapy. However, studies on this topic are often based on therapists’ self-reports: clients’ perceptions are rarely considered. What does “directive approach” mean? Is it what clients prefer? Using cultural psychology and medical anthropology as a theoretical framework, the ethnography explored the experience of psychotherapy from Chinese clients’ perspectives. Specifically, using ethnographic interview, eight informants, two male and six female, ranging in age from 40 to 55, were interviewed twice in-depth about their experiences of seeing Chinese therapists. All informants are Chinese immigrants who reside in a major Canadian city and saw at least one Chinese therapist in a community counselling agency within one year prior to the interview. In the first interview, informants created groups of cards describing a list of hypothesized cultural knowledge regarding psychotherapy. After initial data analysis, the cards were presented to the informants in the second interviews, in which they confirmed and/or rejected the hypotheses by grouping, reorganizing, and ranking the cards. In the end each informant created a number of mind-maps with the cards, which served as a representation of informants’ psychological reality of psychotherapy based on their ordinary language. The maps were then further analysed for themes among informants. Results suggest that clients appreciate therapists who “give homework”, “analyse their problems”, “talk about strategies that other clients have found useful”, “chat”, and “provide resources”. Results also highlight informants’ understanding of their own responsibility for the therapeutic relationship which has never been documented before and has important clinical implications.